Greetings from Trinidad, B.W.I. - (:unkn) unknown (H.O. Thomas, Trinidad, 2010)
Description on the back of the postcard: "The Immortelle in full bloom. This tree is largely used as shade for the cocoa plant." Affixed to the postcard is a 12 cents Trinidad and Tobago postage stamp. The card is postmarked March 1960 and numbered 15034.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Flowers--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Housing, Rural--Trinidad and Tobago; Trees--Trinidad and Tobago; 1960